High temperature stress tolerance in Indian mustard (Brassica juncea) germplasm as evaluated by membrane stability index and excised-leaf water loss techniques - Bhagirath Ram; HS Meena; VV Singh; BK Singh; J Nanjundan; Arun Kumar; SP Singh; NS Bhogal; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
A total of 796 Indian mustard [Brassica juncea (L.) Czern and Coss.] germplasm accessions including 4checks were evaluated in augmented block design for their per se performance with respect to their hightemperature stress tolerance at seedling stage. The traits assessed were percent population survival at 10and 25 days after sowing, percent membrane stability index, percent relative water content, percent excisedleafwater loss, percent oil content, 1000- seed weight (g) and seed yield per plant (g). Eighty seeds of eachgermplasm including four checks were sown in the field under heat stress (26th September) conservedmoisture conditions during Rabi 2012-13 in single rows of two metre length. Among all germplasmaccessions tested, only 48 germplasm accessions were identified on the basis of percent population survivalat 10 DAS (41.00C maximum temperature at 0-10 cm depths), and 25 DAS (40.20C maximum temperatureat 0-10 cm depths). Correlation coefficients between seed yield per plant and heat stress traits indicated thatseed yield per plant was positively associated with membrane stability index (r=0.282*), and 1000 seedweight (r=0.417**). On the basis of per se performance, germplasm accessions DRMR-1574, DRMR-1624,DRMR-1600, DRMR-1799 and Urvashi found to be tolerant to heat stress could be included in the breedingprogramme genotypes for high temperature stress conditions.